A SEMIOTIC STUDY OF TRAFFIC SIGNS - FATMAWATI, ANDRIANI (2011)
This study is aimed at describes about traffic signs. The objetives of study are; (1) to analyze the shape of traffic signs; (2) to analyze the sign or letter of traffic signs; (3) to analyze the color of traffic signs; (4) to describe the meaning of the symbols used in traffic signs. The data sources in this research are all in forms of the pictures that contain symbol used in traffic signs. The data for this study are taken from "HIMPUNAN KEPUTUSAN MENTERI PERHUBUNGAN" which was published in 1993. The type of research employed in this study is descriptive qualitative: it describes information concerning with phenomena of traffic sings. In this research, the object of this study is traffic signs, which are in the forms of signs and letter. In this research, the researcher collects the data through method of; 1) reading the books of the traffic signs; (2) selecting the symbol found in the traffic signs; (3) classifying traffic signs according four types of information traffic signs. Based on the analysis of the conclusions of this study is: (1) The shape of the traffic signs. There are 11 shapes used in traffic sign images. Namely: rectangle diamond, rectangle, miscellaneous, octagon, equilateral triangle with one point down ward, pennant, round, round with diagonal bar, rectangle with longer dimension horizontal, rectangle with linger dimension horizontal and diagonal bar, and rectangle with longer dimension horizontal and isosceles triangles; (2) The sign or letter of traffic signs. The sign or letter of traffic signs in this study includes direction of turn, bend, location information, directions, and restrictions. (3) The color of traffic signs. The colors of traffic signs in this study includes Yellow, it is always associated with a danger or careful sign; Black, color informs the signal of dead for east culture in here; Red is always associated with a danger or careful sign; Green is always associated with earth, environment, growth, relaxation, stabilization and hope; Blue. It is familiar with wealth and peace; White. It is familiar with assosiated with hospital, especially doctor and nurse. For western countries, it is the color of mourning and funeral; and Brown. It is familiar with land, world, neutral, safety and warm. The symbols used in traffic signs represent. There are some symbols used in traffic sign images. Some symbols found in this study were: Non-motorized Vehicles; a picture of transverse trumpets; Motor vehicles; pictures of people; a bicycle picture; pedicab images; working machine image; two-wheeled pedicab and cart.